Improved outcome after hip fracture surgery in Norway: 10-year results from the Norwegian Hip Fracture Register - Jan-Erik Gjertsen; Eva Dybvik; Ove Furnes; Jonas M Fevang; Leif I Havelin; Kjell Matre; Lars B Engesæter (Acta Orthopaedica, 2017)
Background and purpose — The operative treatment of hip fractures in Norway has changed considerably during the last decade. We used data in the Norwegian Hip Fracture Register to investigate possible effects of these changes on reoperations and 1-year mortality. Patients and methods — 72,741 femoral neck (FFN) fractures and trochanteric fractures in patients 60 years or older were analyzed. The fractures were divided into 5 time periods (2005–2006, 2007–2008, 2009–2010, 2011–2012, 2013–2014). Cox regression models were used to calculate unadjusted and adjusted (age group, sex, and ASA class) relative risks (RRs) of reoperation and of 1-year mortality in the different time periods. Results — For undisplaced FFNs treatment with hemiarthroplasty increased from 2.1% to 9.7% during the study period. For displaced FFNs treatment with arthroplasty increased from 56% to 93%. The use of intramedullary nails increased from 9.1% to 26% for stable 2-fragment (AO/OTA A1) trochanteric fractures, from 15% to 33% for multifragment (AO/OTA A2) trochanteric fractures, and from 27% to 61% for intertrochanteric fractures (AO/OTA A3)/subtrochanteric fractures. Compared with the first time period the adjusted 1-year RR for reoperation was 0.43 (95% CI: 0.37–0.49) for displaced FFNs in the last time period. The adjusted 1-year mortality in the last time period was lower for all fractures (RR: 0.87 (0.83–0.91)), displaced FFNs (RR: 0.86 (0.80–0.93)), AO/OTA A1 trochanteric fractures (RR: 0.79 (0.71–0.88)), and AO/OTA A2 trochanteric fractures (RR: 0.87 (0.77–0.98)) when compared with the first study period. Interpretation — Hip fracture treatment in Norway has improved: The risk of reoperation and the 1-year mortality after displaced femoral neck fractures have decreased over a 10-year period. National registration is useful to monitor trends in treatment and outcomes after hip fractures.